Soluble immunoglobulin A in breast milk is inversely associated with atopic dermatitis at early age: the PASTURE cohort study. Issue 1 (January 2014) - Orivuori, L.; Loss, G.; Roduit, C.; Dalphin, J.‐C.; Depner, M.; Genuneit, J.; Lauener, R.; Pekkanen, J.; Pfefferle, P.; Riedler, J.; Roponen, M.; Weber, J.; et al.
Summary Background The role of breastfeeding for the development of atopic diseases in childhood is contradictory. This might be due to differences in the composition of breast milk and levels of antimicrobial and anti‐inflammatory components. Objective The objective of this study was to examine whether levels of total immunoglobulin A (IgA) or transforming growth factor‐β1 (TGF‐β1) in breast milk were associated with the risk of developing atopic dermatitis (AD), atopic sensitization or asthma at early age taking breastfeeding duration into account. Methods The birth cohort study PASTURE conducted in Finland, France, Germany and Switzerland provided 610 breast milk samples collected 2 months after delivery in which soluble IgA (sIgA) and TGF‐β1 levels were measured by ELISA. Duration of breastfeeding was assessed using weekly food frequency diaries from month 3 to month 12. Data on environmental factors, AD and asthma were collected by questionnaires from pregnancy up to age 6. Atopic status was defined by specific IgE levels in blood collected at the ages of 4 and 6 years. Multivariate logistic regression models were used for statistical analysis. Results Soluble IgA and TGF‐β1 levels in breast milk differed between countries, and sIgA levels were associated with environmental factors related to microbial load, for example, contact to farm animals or cats during pregnancy, but not with raw milk consumption. sIgA levels were inversely associated with AD up to the of age 2 years (P‐value for adjusted linear trend: 0.005), independent of breastfeeding duration. The dose of sIgA ingested in the first year of life was associated with reduced risk of AD up to the age of 2 (aOR, 95% CI: 0.74; 0.55–0.99) and 4 years (0.73; 0.55–0.96). No clear associations between sIgA and atopy or asthma up to age 6 were observed. TGF‐β1 showed no consistent association with any investigated health outcome. Conclusion and Clinical Relevance IgA in breast milk might protect against the development of AD.